1983
DOI: 10.1093/bja/55.11.1103
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Early Fibreoptic Bronchoscopy After Aspiration of Gastric Contents

Abstract: Fibreoptic bronchoscopy was undertaken in 26 patients upon hospital admission, to assess if they were suffering from pulmonary lesions subsequent to the aspiration of gastric contents. In 24 of these patients erythematous lesions were observed (sensitivity of the procedure: 92.3%), mainly on the carina. Distal to the carina, the lesions were observed less frequently. The procedure caused no complications in any of the patients studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Of the eight EOP-NR patients with vomiting and impaired vigilance, three died in hospital, two improved later without change of antibiotic drugs, whereas in the remaining three change to the following antibiotic medications was effective: fluconazole (n = 2), imipenem (n = 1), vancomycine (n = 1). Two of these eight EOP-NR patients fulfilled clinical and bronchoscopic criteria of pneumonitis due to gastric acid aspiration [16,18].…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight EOP-NR patients with vomiting and impaired vigilance, three died in hospital, two improved later without change of antibiotic drugs, whereas in the remaining three change to the following antibiotic medications was effective: fluconazole (n = 2), imipenem (n = 1), vancomycine (n = 1). Two of these eight EOP-NR patients fulfilled clinical and bronchoscopic criteria of pneumonitis due to gastric acid aspiration [16,18].…”
Section: Resultsmentioning
confidence: 99%
“…In critically ill patients, the use of bronchoscopy has greatly increased, with both diagnostic and therapeutic goals, such as diagnosis of aspiration pneumonitis, hemoptysis, and traumatic tracheobronchial lesions, management of atelectasis, and bacteriologic diagnosis of nosocomial pneumonia (11,12,17). Although its role following cardiopulmonary transplantation has also been recognized (18), fiberoptic bronchoscopy has not yet been evaluated in brain-dead organ donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of lung donors in our study is too small to draw any strong conclusion and only a large multicenter prospective study could determine the consequence of each main fiberoptic bronchoscopic diagnosis on the recipient outcome. Some investigators have suggested that serial chest X-ray and arterial blood gas analyses should be performed to detect contraindication for lung harvesting (12). This recommendation is probably of some value, but we do not consider that it could replace bronchoscopy; alterations in serial chest X-rayand/or arterial blood gas analysis could not occur because of the short time lapse between the diagnosis of brain death and organ harvesting as early as possible, and undue preparation of the potential recipient and transplantation team is time and energy consuming, and associated with emotional problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations